2022
DOI: 10.3390/v14020193
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Pathogenicity by Coinfection and Sequential Infection with NADC30-like PRRSV and PCV2 in Post-Weaned Pigs

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus (PCVs) are two major viruses that affect pigs. Coinfections between PRRSV and PCV2 are frequently reported in most outbreaks, with clinical presentations involving dyspnea, fever, reduced feed intake, weight loss, and death in fattening pigs. The NADC30-like PRRSV and PCV2d are the main circulating virus strains found in China. This study determines the impact of NADC30-like PRRSV and PCV2d mono-infection and coinfection on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous studies on the effects of co-infection of PRRSV and PCV2 on pigs had different findings. Jinyong Zhang et al, found that the serum concentrations of IFN-γ in pigs co-infected with PRRSV and PCV2 were significantly higher than those in the control group [ 53 ]. Peihu Fan’ team discovered that the HP-PRRSV/PCV2 co-infection group had up-regulated serum concentrations of TNF-α and IL-10, while IFN-γ was lower in the co-infection groups, especially the HP-PRRSV/PCV2 group, than in the single-infection groups [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of co-infection of PRRSV and PCV2 on pigs had different findings. Jinyong Zhang et al, found that the serum concentrations of IFN-γ in pigs co-infected with PRRSV and PCV2 were significantly higher than those in the control group [ 53 ]. Peihu Fan’ team discovered that the HP-PRRSV/PCV2 co-infection group had up-regulated serum concentrations of TNF-α and IL-10, while IFN-γ was lower in the co-infection groups, especially the HP-PRRSV/PCV2 group, than in the single-infection groups [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection of PCV2 or PCV3 with PPV leads to severe viremia and reproductive disorders [ 33 , 34 , 35 ]. In addition, PCV-2 infection inhibits the response of immune-related signaling pathways and promotes the replication of viruses such as pseudorabies virus and porcine reproductive and respiratory syndrome virus [ 36 , 37 ]. Worse still, duck circovirus also causes immunosuppression, and coinfection with other pathogens can lead to serious consequences [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other Korean research teams have demonstrated that positive rates of PCV3 in whole blood, serum, and nasal swabs (Dhandapani et al, 2021) and whole blood (Song et al, 2021) samples of wild boars were 5.6% and 0.01 %, respectively. Although we cannot rule out the possibility of other influences, these rapidly increasing positive rates of PCV3 in this study might be due to sample differences (Kixmöller et al, 2008;J. Zhang et al, 2022).…”
Section: ) the Discrepancy Of The Target Cells Between Pcv2 And Pcv3mentioning
confidence: 71%